Developing an English Syllabus for Kindergarten Students in Jember - Khumaidah, Sofkhatin (Fenomena, 2004)
The absence of a standardized English syllabus for kindergartens in Indonesia, particularly in Jember, poses a critical challenge, as English is increasingly taught at the preschool level despite the lack of a government mandate. This issue falls within broader debates on early foreign language learning and syllabus design, where young learners’ cognitive and linguistic characteristics demand age-appropriate, concrete content. This study aims to develop a practical English syllabus for regular kindergartens where Bahasa Indonesia is the instructional language. Using a developmental research approach, the researcher conducted needs surveys via questionnaires and interviews with experts, kindergarten teachers, parents, and elementary English teachers, as young children could not serve as direct informants. The resulting product is a lexicon-based syllabus that emphasizes oral vocabulary building through twenty topics, including numbers, colors, animals, family, and feelings, spread over thirty-four meetings with simple, fun activities such as singing and movement. The syllabus was tested, evaluated, and revised, showing strong alignment with objectives and high interest among preschoolers. The study concludes that the syllabus effectively guides the introduction of English in non-English-speaking environments and recommends that teachers use it flexibly and that future researchers focus on developing affordable teaching media. Tidak adanya silabus bahasa Inggris yang terstandarisasi untuk taman kanak-kanak (TK) di Indonesia, khususnya di Jember, merupakan tantangan krusial di tengah meningkatnya pengajaran bahasa Inggris di tingkat prasekolah meskipun tanpa mandat pemerintah. Isu ini berada dalam perdebatan yang lebih luas tentang pembelajaran bahasa asing pada usia dini dan desain silabus, di mana karakteristik kognitif dan linguistik anak usia dini memerlukan materi yang konkret dan sesuai usia. Penelitian ini bertujuan mengembangkan silabus bahasa Inggris yang praktis untuk TK regulur dengan bahasa pengantar Bahasa Indonesia. Dengan menggunakan prosedur penelitian pengembangan, peneliti melakukan survei kebutuhan melalui kuesioner dan wawancara dengan para ahli, guru TK, orang tua, dan guru bahasa Inggris SD, karena anak-anak tidak dapat menjadi informan langsung. Produk yang dihasilkan adalah silabus berbasis leksikal yang menekankan pengucapan kosa kata lisan melalui dua puluh topik, seperti angka, warna, binatang, keluarga, dan perasaan, dalam 34 pertemuan dengan aktivitas sederhana dan menyenangkan seperti bernyanyi dan bergerak. Silabus ini telah diujicobakan, dievaluasi, dan direvisi, dan menunjukkan kesesuaian yang tinggi dengan tujuan serta minat anak yang kuat. Penelitian ini menyimpulkan bahwa silabus tersebut secara efektif memandu pengenalan bahasa Inggris di lingkungan non-penutur asli, dan merekomendasikan guru untuk menggunakannya secara fleksibel serta peneliti selanjutnya untuk fokus pada pengembangan media pembelajaran yang terjangkau.